Rapid formulation of redox-responsive oligo-β-aminoester polyplexes with siRNA via jet printing - Lovato, Tatiana; Taresco, Vincenzo; Alazzo, Ali; Sansone, Catarina; Stolnik, Snjezana; Alexander, Cameron; Conte, Claudia (Royal Society of Chemistry, 2018)
Here we describe a rapid inkjet formulation method for screening newly-synthesised cationic materials for siRNA delivery into cancer cells. Reduction responsive oligo-β-aminoesters were prepared and evaluated for their ability to condense siRNA into polyplexes through a fast inkjet printing method. A direct relationship between the oligomer structures and charge densities, and the final cell response in terms of uptake rate and transfection efficacy, was found. The oligo-β-aminoesters were well-tolerated by the cancer cells, compared to conventional cationic polymers so far employed in gene delivery, and were as active in silencing of a representative luciferase gene.